Condition of Seagrass at Prawean Beach, Jepara, Based on the Seagrass Ecological Quality Index (SEQI) - S. Wahyuni, Endang; Edy Yuwono; Sri Handayani (Universitas Nasional Jakarta, 2025)
This study aims to investigate the bioecology of seagrass at Prawean Beach, Jepara, through analysis of species composition, the Seagrass Ecological Quality Index (SEQI), environmental water parameters, as well as the connection between environmental variables and seagrass cover. Data collection was carried out in September at two stations using the method transect-quadratic, while the physical-chemical parameters water were measured in situ and analyzed in a way statistically. Research results show that Thalassia hemprichii is the dominant species with the highest coverage in all point observations, while Enhalus acoroides, Cymodocea rotundata, and Halodule uninervis have lower cover more low. The SEQI value is in the range of 45–50% which indicates a quality ecosystem in category medium. Analysis Spearman correlation reveals that brightness influential significant to cover seagrass (r = 0.82; p = 0.048), whereas salinity, temperature, DO, pH, nitrate, and phosphate show no significant connection. Findings This indicates that disturbance of the physical coast potential becomes factor main influencing factor health field of seagrass at Prawean Beach.